2019
DOI: 10.1128/mbio.02774-19
|View full text |Cite
|
Sign up to set email alerts
|

The Staphylococcus aureus Transcriptome during Cystic Fibrosis Lung Infection

Abstract: Although bacteria have been studied in infection for over 100 years, the majority of these studies have utilized laboratory and animal models that often have unknown relevance to the human infections they are meant to represent. A primary challenge has been to assess bacterial physiology in the human host. To address this challenge, we performed transcriptomics of S. aureus during human cystic fibrosis (CF) lung infection. Using a machine learning framework, we defined a “human CF lung transcriptome signature”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 57 publications
3
45
1
Order By: Relevance
“…Recently, two studies have utilized RNA-Seq to examine the transcriptional response of S. aureus in vivo . Work by Ibberson and Whiteley examined the S. aureus transcriptome in the lung of patients with cystic fibrosis (CF) ( 14 ), while Deng et al examined the S. aureus transcriptome during vaginal colonization ( 15 ). The RNA-Seq data sets for these two studies were not yet available at the time that we performed the original search of the GEO database (for our global sRNA expression analysis described above).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two studies have utilized RNA-Seq to examine the transcriptional response of S. aureus in vivo . Work by Ibberson and Whiteley examined the S. aureus transcriptome in the lung of patients with cystic fibrosis (CF) ( 14 ), while Deng et al examined the S. aureus transcriptome during vaginal colonization ( 15 ). The RNA-Seq data sets for these two studies were not yet available at the time that we performed the original search of the GEO database (for our global sRNA expression analysis described above).…”
Section: Resultsmentioning
confidence: 99%
“…In vivo RNA-Seq data sets were acquired from GEO under accession number SRP222773 for CF data and accession number SRP229518 for vaginal data ( 14 , 15 ). For the CF lung data, sRNA expression values (in RPKM) from nine clinical isolate samples were averaged and compared to the averaged sRNA expression values from nine S. aureus cultures grown in chemically defined media (CDM) as well as to those from nine samples from synthetic cystic fibrosis media (SCFM).…”
Section: Methodsmentioning
confidence: 99%
“…Most significantly, GRIM neutrophils were also found to have reduced bacterial killing capacity, which aligns with the apparent disconnect between NE release and inability to resolve infection in CF airways (89). More recent studies have reported how Staphylococcal superantigen-like protein 13 (SSL13) from Staphylococcus aureus, a common early CF pathogen, can induce neutrophil exocytosis (91) and whose production is evident in the CF microbiome (92). In an age related cohort of non-CF children admitted for acute respiratory distress syndrome (ARDS), neutrophil exocytosis and reduced bacterial killing was observed in individuals co-infected with virus and bacteria but not viral infection alone, suggesting that neutrophil exocytosis may be linked to responses against polymicrobial infection (93).…”
Section: Neutrophil Exocytosismentioning
confidence: 68%
“…These strategies, in combination with its fully functional motility, may explain the presence of P. aeruginosa in the deep tissue instead of the wound surface, which is predominantly colonized by S. aureus and S. epidermidis 41 . In a recent study of cystic fibrosis sputum samples, S. aureus was found to be metabolically active in the presence of P. aeruginosa 81 . These results are contrary to the known paradigm that S. aureus is metabolically less active in the presence of P. aeruginosa , forms small colony variants (SCVs), and therefore evades the antibiotics 82 .…”
Section: Cross‐talk In the Quorummentioning
confidence: 99%